Broccoli Effects on Hif-1 A in Spermatozoa Cells of Ratsthat Induces Psychological Stress - Ahmad Nur Huda; Bambang Wirjatmadi; Bambang Purwanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
ff